2017
DOI: 10.14503/thij-16-6027
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Patent Foramen Ovale in Exacerbating Hypoxemia in Chronic Pulmonary Disease

Abstract: Patent foramen ovale has been associated with multiple pulmonary diseases, such as pulmonary hypertension, platypnea-orthodeoxia syndrome, and chronic obstructive pulmonary disease. A connection between patent foramen ovale and chronic pulmonary disease was first described more than 2 decades ago in case reports associating patent foramen ovale with more severe hypoxemia than that expected based on the severity of the primary pulmonary disease. It has been suggested that patients with both chronic pulmonary di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Fenster et al 2 performed a study where 97 patients with underlying chronic pulmonary disease had an improvement in NYHA functional class (51% of patients; P < 0.001) and reduced supplemental oxygen requirements (34% of patients; P < 0.001) after PFO closure. 1 Closing the PFO in the setting of a PE can yield similar effects as seen in patients with other lung disease. Our patient suffered from low oxygen saturation due to the PE, which worsened from the R-L shunting through the PFO after endotracheal intubation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fenster et al 2 performed a study where 97 patients with underlying chronic pulmonary disease had an improvement in NYHA functional class (51% of patients; P < 0.001) and reduced supplemental oxygen requirements (34% of patients; P < 0.001) after PFO closure. 1 Closing the PFO in the setting of a PE can yield similar effects as seen in patients with other lung disease. Our patient suffered from low oxygen saturation due to the PE, which worsened from the R-L shunting through the PFO after endotracheal intubation.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, in the setting of a chronic obstructive pulmonary disease (COPD), a patient with PFO will have an increase in rightsided heart pressures resulting in hypoxemia. Michael et al 1 reported that PFO found in 12 of 22 patients with COPD had an increased chance of hypoxemia compared to patients without PFO. In these patients, PFO closure was associated with an improvement of SaO2 (10.1% average improvement; P < 0.001) and an improvement in the New York Health Association (NYHA) functional class (1.5 median improvement in class; P = 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…While persistent post-dive hypoxemia may have multiple causes: (1) ventilation/perfusion mismatch due to atelectasis ( Fahlman et al, 2009 ; Schipke et al, 2019 ). (2) increased right-to-left shunt; via increased strain on the right ventricle ( Scherhag et al, 2005 ) and/or chronic pulmonary hypertension ( Vestin, 2015 ), so if right atrial pressure becomes higher than left atrial pressure right-to-left shunting can occur ( Layoun et al, 2017 ). A third cause could be diffusion limitation due to increased extravascular lung water ( Picano et al, 2006 ; Boussuges et al, 2011 ; Picano and Pellikka, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptogenic stroke is associated with a high-risk PFO score (≥2), which includes a Chiari network ( 7 ). However, PFO closure has been found to be beneficial in a variety of cases, such as reducing recurrent stroke or transient ischemic attacks compared with medical therapy ( 8 ), alleviating symptoms in patients with platypnea-orthodeoxia ( 9 ), and can potentially improve quality of life in patients with chronic obstructive pulmonary disease with hypoxemia ( 10 ).…”
Section: Discussionmentioning
confidence: 99%